On the reinstatement of R. samoensis and R. brevistyla in East Pacific red mangroves (Rhizophora, Rhizophoraceae) (Revista Científica Ciencias Naturales y Ambientales, 2023)
On the basis of previously presented molecular studies, Rhizophora samoensis (Hochr.) Salvoza and R. brevistyla Salvoza (Rhizophoraceae) are here reinstated as valid names for the Eastern Pacific red mangroves. The identical meaning of vernacular names of R. samoensis from Samoa and coastal Ecuador is here reported for first time. The lectotype of the basionym Rhizophora mangle var. samoensis is designated.
Keywords: Lectotype; Mangal; Pacific ocean; Transoceanic; Vernacular names